2008
DOI: 10.4102/curationis.v31i1.903
|View full text |Cite
|
Sign up to set email alerts
|

Working conditions that contribute to absenteeism among nurses in a provincial hospital in the Limpopo Province

Abstract: Absenteeism results in an increased workload for nurses who stand in for colleagues and can lead to situations in which a lack of motivation among nurses and a lowering of the quality of patient care may occur. The researcher observed that certain conditions, such as inflexible working schedules, were given as reasons for the absenteeism in units in a provincial hospital. A non-experimental, descriptive, quantitative study was undertaken. The purpose of the article was to describe the working conditions that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
10

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 29 publications
(1 reference statement)
2
23
0
10
Order By: Relevance
“…Outras pesquisas corroboram estes resultados (8,13,15) , e indicam a provável associação das LS com as atividades profissionais, em especial, na assistência direta ao paciente. Quanto à faixa etária, estudo (14) concluiu que a idade não condiciona as ausências por LS.…”
Section: Discussionunclassified
“…Outras pesquisas corroboram estes resultados (8,13,15) , e indicam a provável associação das LS com as atividades profissionais, em especial, na assistência direta ao paciente. Quanto à faixa etária, estudo (14) concluiu que a idade não condiciona as ausências por LS.…”
Section: Discussionunclassified
“…This indicates that nurses who felt they were successful and able to achieve their goals were less absent from work. While it has been acknowledged that absenteeism places extra pressure on nurses who stand in for absent colleagues [60] , it has been suggested that absenteeism may help to prevent burnout, allowing the nurse to return to work with renewed strength [19] . Absenteeism gives the nurse time away from the stressful work environment, provides the opportunity to engage social support mechanisms and allows the nurse the time to address his or her feelings of burnout.…”
Section: Discmentioning
confidence: 99%
“…Outras sugestões para redução do absenteísmo foram apontadas, destacando-se as que examinaram a sobrecarga de trabalho e a relação com o aumento de licenças saúde e quantificaram a perda de dias em razão da carga de trabalho, utilizando um sistema de classificação de pacientes (Rauhala et al, 2007 Marziale, 2006;Rogenski;Fugulin, 2007;Rauhala et al, 2007;Laus;Anselmi, 2008;Inoue at al 2008;Bernardino;Ribeiro, 2008;Nyathi;Jooste, 2008;Costa;Sena, 2009;Campos;Juliani;Palhares, 2009;Abreu;Simões, 2009;Sancinetti et al, 2009;Griep et al, 2010 (Minayo, 2006;2012 A técnica é realizada com a presença de um moderador e de um ou dois relatores ou observadores, com papéis e funções específicas. Ao moderador cabe orientar e coordenar o debate, facilitar a participação da discussão, evitar a monopolização da fala em detrimento de outra, estimular a discussão para obter relatos, sentimentos e experiência, preferências, criando ambiente facilitador, propicio a apresentação de diferentes pontos de vista, evitar constrangimentos, exaltação ou arrefecimento de ânimos, sem exercer nenhum tipo de pressão para que se estabeleça um plano conclusivo.…”
Section: O Processo De Assistência à Saúdeunclassified
“…[ Estudo que analisou as ações gerenciais dos enfermeiros frente às ausências do pessoal de enfermagem corrobora o resultado desta pesquisa ao evidenciar ações gerenciais como a de verificar, inicialmente, por meio de escala, o número de servidores disponíveis; fazer a convocação de um profissional para substituição do colaborador faltoso e redistribuir as atividades concluindo, ser possível, estabelecer ações programadas em caso de faltas (Parra, Melo, 2004 (Nyathi, Jooste, 2008). A convocação de um colaborador de outra unidade, pela pouca integração com a equipe, pode não ser aconselhada (Cicolella, 2004 [...] trocar folga (S13).…”
Section: Análise Quantitativa Do Ano De 2011unclassified
See 1 more Smart Citation